Pu-erh tea polysaccharides decrease blood sugar by inhibition of α-glucosidase activity in vitro and in mice. Issue 5 (13th May 2015) - Deng, Yea-Tyz; Lin-Shiau, Shoei-Yn; Shyur, Lie-Fen; Lin, Jen-Kun
<x xml:space="preserve">Abstract</x> In this report we describe a group of carbohydrates found in pu-erh tea polysaccharide (PTPS) that can decrease blood sugar by inhibiting alpha-glucosidase.